Review: Ocular Complications of Mosquito-Transmitted Diseases - Segu, Bhagya; Riese, Nicole Auchter; Nguyen, Kim Thien Hong; Leung, Michael; Segu, Pat (Canadian Journal of Optometry, 2018)
The World Health Organization estimates that 1 billion cases of infectious disease originate from vector transmission, resulting in several million deaths annually. Mosquitos are the primary vector for multiple diseases in humans that cause self-limiting to sight-threatening ocular complications and significant systemic illness. The 2015-2016 outbreak of the mosquito-borne Zika virus in North and South America brought to the forefront how quickly mosquitoes can spread disease between continents, especially among vulnerable patient populations. Optometrists should be familiar with the associated ocular complications in order to effectively diagnose, co-manage, treat, and educate patients who have been infected by mosquito-borne disease. This paper reviews the ocular manifestations of mosquito-transmitted diseases including Zika virus, West Nile virus, Malaria, Dengue fever, Chikungunya, and Dirofilaria.